2010
DOI: 10.1007/s10549-010-0829-8
|View full text |Cite
|
Sign up to set email alerts
|

Among women who experience a recurrence after postmastectomy radiation therapy irradiation is not associated with more aggressive local recurrence or reduced survival

Abstract: Recent pre-clinical models suggest that radiation can promote tumor aggressiveness. We hypothesized that if this were occurring clinically, locoregional recurrences (LRRs) after postmastectomy radiation therapy (PMRT) would lead to lower survival than LRR after mastectomy alone. This study used two independent data-sets to compare survival after LRR in women treated with versus without PMRT. Data from 229 LRR cases among 1,500 patients enrolled on prospective trials at the MD Anderson Cancer Center (MDA), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In addition, although prior analysis suggests the use of post-mastectomy radiation does not lead to more aggressive LRR (12), the small number of isolated SCV LRR after post-mastectomy radiation make it difficult to generalize to this setting. Indeed, all patients who experience an isolated SCV recurrence after PMRT developed distant disease in less than three years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, although prior analysis suggests the use of post-mastectomy radiation does not lead to more aggressive LRR (12), the small number of isolated SCV LRR after post-mastectomy radiation make it difficult to generalize to this setting. Indeed, all patients who experience an isolated SCV recurrence after PMRT developed distant disease in less than three years.…”
Section: Discussionmentioning
confidence: 99%
“…In prior analysis of the British Columbia Cancer Agency randomized data from the post-mastectomy radiation versus none trial (11), we compared outcomes among patients who experienced a LRR after post-mastectomy radiation to those who experienced a LRR after mastectomy alone and demonstrated no difference in overall survival based on prior post-mastectomy radiation (12). The same was observed for isolated LRR in the patient cohort being examined herein in spite of the non-randomized use of post-mastectomy being associated with higher risk characteristics of the presenting disease in these data (12). For this reason, the patients who had prior post-mastectomy radiation and those who did not were combined for this analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Despite salvage treatment, long-term survival after LRR is poor, with 10-year survival of *30% [1]. Even in women where distant disease does not occur, the onset of LRR is emotionally devastating and results in significant morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…This effect has been previously termed tumor bed effect [10,11]. A recent study analyzing retrospective datasets, however, reported that recurrences after postmastectomy radiation therapy are not associated with more aggressive local behaviors or reduced survival compared to patients recurring after mastectomy only [12]. Thus, at this point this question remains open and controversial.…”
Section: Introductionmentioning
confidence: 99%